The Influence of Wordwall Learning Media on the Interest and Learning Outcomes of Students at Muhammadiyah 1 Vocational School, Pekanbaru - Asri Neli Putri; Giska Putri Yani; Suparmi Suparmi (Journal of Innovative and Creativity, 2025)
Low student learning interest and learning outcomes that have not yet reached the Minimum Competency Criteria (KKM) are challenges in accounting learning at SMK Muhammadiyah 1 Pekanbaru. This study aims to determine the effect of using Wordwall learning media on improving student interest and learning outcomes in grades XI AKL and XI MPLB. The research subjects consisted of two classes, namely the experimental class and the control class. The method used was quantitative with a quasi-experimental design of the nonequivalent control group design. Data collection techniques included a learning interest questionnaire, observation of student activities, and learning outcome tests (pre-test and post-test). The data analysis technique used the t-test (independent sample t-test) with the help of SPSS software. The results showed that there was a significant effect of using Wordwall media on improving student interest and learning outcomes. The average post-test score in the experimental class increased to 85, higher than the control class. In addition, student learning interest scores also increased significantly with a significance value of 0.000 (<0.05). Wordwall media has been proven effective in increasing student engagement, conceptual understanding, and academic achievement in accounting learning.